Front Cover. Issue 5 (2nd May 2021) - Peyvasteh, Motahareh; Popov, Alexey; Bykov, Alexander; Pierangelo, Angelo; Novikova, Tatiana; Meglinski, Igor
Abstract: The possibilities of using Mueller matrix (MM) imaging polarimetry to assess meat quality have not yet been sufficiently explored. In the current study, the fresh porcine muscles are imaged at room emperature with a wide‐field MM imaging polarimeter over 26 hours to visualize dynamics of tissue optical properties through applying Lu‐Chipman decomposition. The MM images, frequency distribution histograms and statistical analysis of the MM elements show prominent changes over time. Further details can be found in the article by M. Peyvasteh, A. Popov, A. Bykov, A. Pierangelo, T. Novikova, I. Meglinski (e202000376 ) Abstract : The possibilities of using Mueller matrix (MM) imaging polarimetry to assess meat quality have not yet been sufficiently explored. In the current study, the fresh porcine muscles are imaged at room emperature with a wide‐field MM imaging polarimeter over 26 hours to visualize dynamics of tissue optical properties through applying Lu‐Chipman decomposition. The MM images, frequency distribution histograms and statistical analysis of the MM elements show prominent changes over time. Further details can be found in the article by M. Peyvasteh, A. Popov, A. Bykov, A. Pierangelo, T. Novikova, I. Meglinski (e202000376 )